Evaluation of opportunities for the use of modern methods for correction and prevention of risks in the quality control of clinical trials - Kolodyezna, Tetyana; Zupanets, Kateryna; Dobrova, Victoria (ScienceRise: Pharmaceutical Science, 2018)
To organize and conduct a clinical trial (СT) at a high level, it is necessary to continuously monitor its quality, as the occurrence of non-conformances can threaten health and safety of the trial subjects, as well as lead to CT data loss or their unreliability. In general, for the effective CT quality control, it is expedient to continuously improve the quality management system of all parties who participate in the CT, including at the clinical site. Current regulatory requirements include an indication of the need for a continuous process of the quality management system improvement to ensure the proper level of the process performance, in particular, the system of non-conformances correction and prevention. The aim of this work was to evaluate the possibilities and problems of applying modern methods of risks correction and prevention in the CT quality management. Materials and methods. To achieve the aim of the study, a meta-analysis of literature sources using PICO search technology was carried out and analysis of existing regulatory documents on the availability of methodologies, instructions and algorithms for selecting and applying the non-conformances correction and prevention tools during CT organizing and conducting. Results of the study. The study showed that regulatory authorities see the need for standardized CT quality management systems to increase the number of qualified clinical sites, as well as more strict compliance with the ICH GCP principles. The analysis of regulatory documents showed the absence of unified harmonized requirements for carrying out the processes of correction and prevention of non-conformances within the framework of CT organizing and conducting. Conclusions.Organizing and conducting of CT requires continuous monitoring of the quality of the processes carried out to ensure getting of complete and reliable data on the study drug. Given the lack of regulatory requirements governing the process of non-conformances correction and prevention, it seems expedient to develop an algorithm for work with CAPA-plan and its methodology, as well as SOP to standardize the conduct of this process